TEACHING SPEAKING USING A “SNAKE AND LADDER” BOARD GAME: A TEACHER STORY - Arfani, Sri; Sulistia, Atika (Research And Innovation In Language Learning (RILL), 2019)
The objective of this research is to know how the implementation of Teaching Speaking Using a “Snake and Ladder” Board Game to the students in an English class of a private schools in a Jakarta. Employing descriptive study, the English teacher made her story from her classroom. The data of the research included on-site-observation and recording. The results show that (1) using a snake and ladder board game is potential to promote students’ eagerness to speak within the peers, (2) despite of some difficulties, students seem enjoy the learning, and (3) a “friendly’ learning atmosphere was established.